THE BASIC ANALYSIS OF CONTROL SYSTEMS ON COMMERCIAL AIRCRAFT (Perner's Contacts, 2011)
This paper is aimed at the differences between the control systems on commercial aircraft. Architecture of the particular control systems is given a closer look and in this way based on the analogy method of control system of commercial aircraft we can apply this knowledge of control systems to flight laboratories of the University of Žilina, which are the part of project “Centre of Excellence for Air Transport” ITMS 26220120065.
Keywords: Aerolab; Control systems; Fly-by-wire; Single aisle aircraft; modification of the structure